Profitability, Solvency, and Liquidity: A Comparison between Multinational and Domestic Companies in the Industrial Sector, IDX - Prasetyo, Irwanto; Afara Ross Prawidya (Journal of Advances in Accounting, Economics, and Management, 2024)
Multinational and domestic companies possess distinct operational characteristics and financial strategies, influenced by their access to global markets and ability to manage market risks. This study aims to analyze the differences in profitability (ROE), identify solvency differences (DER), and assess liquidity differences (CR) between multinational and domestic companies. Utilizing a quantitative descriptive approach and a comparative research type, the study samples were determined through purposive sampling methods. Secondary data were derived from the annual reports of multinational and domestic companies in the industrial sector listed on the Indonesia Stock Exchange (IDX) over a five-year period (2019–2023), totaling 40 research samples. Data analysis was conducted using the Independent Sample T-Test comparative test. The findings reveal significant differences in solvency and liquidity variables between multinational and domestic companies. The higher solvency and liquidity levels of multinational companies allow them to better manage risks and shocks in global markets. Conversely, domestic companies show lower solvency and liquidity levels due to limited access to global markets. Meanwhile, the profitability (ROE) variable does not show a significant difference, even though the profitability level of multinational companies tends to be higher than that of domestic companies.